Assessing knowledge, attitudes and behaviours for sustainable development: a case study of Tibet University - Zhimin Chen; Muhammad Rizal Razman; Sharifah Zarina Syed Zakaria; Khai Ern Lee (Discover Sustainability)
Abstract This study was conducted among students of Tibet University to assess their levels of knowledge, attitudes and behaviours related to sustainable development. Based on the Knowledge-Attitude-Practice (KAP) model, this study investigated the mechanism of how university students’ knowledge, attitudes, and behaviors relate to sustainable development. A quantitative survey method was employed, with a questionnaire administered to 251 respondents to assess the levels of students’ knowledge, attitudes and behaviors regarding sustain-able development. SPSS 27.0 was used to analyze differences in sustainable development practices across demographic variables, while AMOS 28.0 was employed to validate the impact of knowledge and attitudes on behavior. The levels of knowledge (x = 3.28), attitude (x = 3.29) and behavior (x = 3.30) toward sustainable development among undergraduate students at Tibet University were found to be in the low to medium range. Comparative analysis of mean behaviors indicated significant differences in sustainable development practices among students based on ethnicity, faculty and residential area. Structural equation modelling confirmed that knowledge and attitudes related to sustainable development have a positive impact on behavior. The mechanism of "knowledge-action transformation" in the theory of education for sustainable development is expected to be better explained by this study, which will also offer a scientific foundation for improving the efficacy of education for sustainable development instruction in ethnically diverse colleges and universities, as well as for developing locally relevant policies.